(untitled) (Mustansiria Dental Journal, 2018)
Smoking is linked to osteoporosis through its anti-estrogenic effect in women which results in premature menopause in smokers and increased bone resorption is correlated with estrogen loss in menopause women. The aim of this study is to evaluate the effects of smoking and hormonal changes on the thickness of mandibular inferior cortex and the dentition status in both maxilla and mandible (DMFT) in menopausal females and to estimate the value of panoramic radiographic findings in assessing the possibility of latent osteoporosis. Panoramic images for 80 healthy, median stature, smokers and non-smokers Iraqi female subjects aged (20-35) years premenopausal and (45-60) years menopause was done, then the thickness of mandibular inferior cortex and (DMFT) was evaluated. The results showed that panoramic radiographic measurements are considered as indicator of bone turnover and the dentist is able to identify smokers and non-smokers postmenopausal females with increase risk of osteopenia and osteoporosis by using dental panoramic radiography which is a simple valuable screening tool.